Does color influence eye movements while exploring videos? - Shahrbanoo Hamel; Dominique Houzet; Denis Pellerin; Nathalie Guyader (Bern Open Publishing, 2015)
Although visual attention studies consider color as one of the most important features in guiding visual attention, few studies have investigated how color influences eye movements while viewing natural scenes without any particular task. To better understand the visual features that drive attention, the aim of this paper was to quantify the influence of color on eye movements when viewing dynamic natural scenes. The influence of color was investigated by comparing the eye positions of several observers eye-tracked while viewing video stimuli in two conditions: color and grayscale. The comparison was made using the dispersion between the eye positions of observers, the number of attractive regions measured with a clustering method applied to the eye positions, and by comparing eye positions to the predictions of a saliency model. The mean amplitude of saccades and the mean duration of fixations were compared as well. Globally, a slight influence of color on eye movements was measured; only the number of attractive regions for color stimuli was slightly higher than for grayscale stimuli. However, a luminance-based saliency model predicts the eye positions for color stimuli as efficiently as for grayscale stimuli.